Studying and analyzing the performance of photovoltaic system by using fuzzy logic controller - Shahir Fleyeh Nawaf; Uzba H. Salman; Mohammad Omar Salih (Bulletin of Electrical Engineering and Informatics, 2022)
The main objective of this paper is to implement a circuit-based simulation model of a photovoltaic (PV) cell in order to investigate the electrical behavior of the practical cell with respect to some changes in weather parameters such as irradiation and temperature. The research focuses on using a simulation model to achieve the maximum power of solar energy by using the maximum power point tracking (MPPT) controller. The circuit simulation model consists mainly of three subsystems: PV cells: DC/DC converter; and MPPT controller-based logic fuzzy control. Dynamic analysis of the system is carried out and the results are recorded. The maximum power control function is achieved with the appropriate power control of the power inverter. Fuzzy logic controller has been used to perform MPPT functions to get maximum power from the PV panel. The proposed circuit was implemented in MATLAB/Simulink and the results show that the output sequence is non-linear and almost constant current to the open circuit voltage and the power has maximum motion to voltage for certain environmental conditions.